THE ANALYSIS OF ENVIRONMENTAL IMPACT BASED ON PRODUCT LIFE CYCLE OF HEADLAMP, SIGNALING AND MARKER LAMP IN VEHICLE - VENA CHAIR (NIM : 231 04 013); Pembimbing : Dr. Ir. Yatna Yuwana M., ANFALUZIA
Product life cycle stages comprise virgin raw materials extraction activities, materials processing, product manufacturing, product use, product end of life through final disposal. The first stage in the life cycle of any process is extraction of resources from their natural reservoirs. The extractive activities considered are those used to produce the consumable resources used throughout the life. Material extraction is the process of retrieving valuable materials from layers of the earthÃ‚Â’s crust such as exploration of crude oil, mining. However, materials which are extracted contain toxic and hazardous substances. Next stage, those materials are used in manufacturing to produce new product for humans benefits. But arisen effects during virgin materials extraction, materials processing and manufacturing are releasing harmful emissions such as dioxin, furan, CO2, SOx, NOx and wastes to environment. At final disposal stage after product end of life stage, post customers products which are considered as wastes incinerated also release harmful emission dioxin, CO2, SOx, NOx and heavy metals. At landfill, remained wastes contain heavy metals which are unbiodegradabled to environment. Consequence, all those stages will affect impact of environment, potential to harm humans and animals health. The purpose of the research is to analyze potential of environmental impact based on life cycle of product of headlamp, signaling and marker lamp in vehicle. Types of materials are used to produce product of headlamp, signaling and marker lamp are 1) thermoplastic: polycarbonate (PC), polymethyl methacrylate (PMMA), polypropylene (PP); 2) elastomer (karet): ethylene-propylene-diene-monomer rubber (EPDM); 3) kaca; 4) lampu tungsten-halogen yang terdiri dari tungsten (wolfram) filament dan gas iodine. PC, PMMA, PP, EPDM and glass also use toxic additives where after end of life stage which is considered products waste if they are incinerated can affect harmful to environmental impact, disrupt humans and animals health. PC is considered very harmful because contain bisphenol-A and PMMA also considered harmful because contain methyl methacrylate (MMA) which disrupt human health. Whereas, PP contain propylene which is not identified harmful to human health disrupter, such as carninogen, mutagen, reproductive system, growth, neurotoxicant, endocrine gland. Raw materials of glass comprise silica-crystalline (SiO2), soda as (Na2CO3), limestone (CaCO3) where silica-crystalline can affect silicosis (lung cancer) to human and animals health.